Wild gingers (Zingiberaceae) at Sungai Kangkawat, Imbak Canyon Conservation Area (ICCA), Sabah - Suganthi Appalasamy; Nivaarani Arumugam; Lam, Yee Fan; Nor Azizun Rusdi (Universiti Malaysia Sabah, 2020)
This study was carried out during the Geographic Borneo Expedition in 2018 (28 September – 3 October 2018) with the objective to assess the diversity of gingers (Zingerberaceae) at Sungai Kangkawat, Imbak Canyon Conservation Area (ICCA). Four tracks were surveyed, namely, Sungai Kawang, Nepenthes, South Rim and Pelanjau. Any ginger clump along these tracks were visually searched and sampled. The plants (stems, leaves and rhizomes) together with their flowers and fruits, if present, were collected, labelled and kept in a ziplock bag for herbaria preparation and identification. Information on ecology, habitat and location coordinates of each species were also recorded. Species identification was carried out using published taxonomic keys and pictures of the plants. There were 11 genera found along Sungai Kawang track, seven along Nepenthes track, three along South Rim track, and five along Pelajau track. Previous unpublished expedition report stated that there were 48 ginger species in ICCA. However, in the present study, only 28 known species from 11 genera were found. The low number of species was associated with difficulty to identify the ginger samples, as many were lacking flowers, probably due to the lapse of the flowering season.